Aflatoxin Growth versus Safe Pre- and Post-Harvest Drying and Storage - Villers , Philippe (Journal of Postharvest Technology, 2015)
Discussed are field tested solutions including Ultra Hermetic storage™  contributing to solving the dual global issues of reducing food losses and  protecting food safety during drying and storage of grains in a world of  growing climate change.Data is provided on post harvest losses, on the public  health hazard posed by aflatoxins, and how these problems are aggravated by  hot, humid climates. Field data on drastically reducing growth of aflatoxins in  storage is described. The storage requirements for moisture control and oxygen  levels are specified for pesticide-free storage using airtight storage, including  hermeticity requirements needed. Such systems are now used in 107 countries.  Benefits include major storage loss reduction – typically to less than 1% for up  to 1-year of storage even in the tropics, as compared to typical losses up to  25%, and the inhibition of growth of aflatoxin-producing molds. Data on the  application of the same technology to safe, multi-month seed storage without  refrigeration as documented by the IRRI and others. Quantitative data is  presented. Comparison of conventional storage, air-conditioned and  refrigerated storage with Ultra Hermetic storage is provided.Also described are  the available forms of both Ultra Hermetic Storage and improved solar drying  for cost effective solutions to improve both farmer income and nutrition during  what many developing countries refer to as the “starving season”. This helps  solve food insecurity with increased abilities to preserve commodities in good  condition for up to a year or more, as well as facilitate exports by meeting  international standards.
Keywords: Aflatoxins; Cocoon™; Hermetic Storage Solar Drying; Ultra Hermetic™